Experimental realization of two-dimensional Dirac nodal line fermions in monolayer Cu2Si. Issue 1 (December 2017) - Feng, Baojie; Fu, Botao; Kasamatsu, Shusuke; Ito, Suguru; Cheng, Peng; Liu, Cheng-Cheng; Feng, Ya; Wu, Shilong; Mahatha, Sanjoy; Sheverdyaeva, Polina; Moras, Paolo; Arita, Masashi; et al.
Abstract Topological nodal line semimetals, a novel quantum state of materials, possess topologically nontrivial valence and conduction bands that touch at a line near the Fermi level. The exotic band structure can lead to various novel properties, such as long-range Coulomb interaction and flat Landau levels. Recently, topological nodal lines have been observed in several bulk materials, such as PtSn4, ZrSiS, TlTaSe2 and PbTaSe2 . However, in two-dimensional materials, experimental research on nodal line fermions is still lacking. Here, we report the discovery of two-dimensional Dirac nodal line fermions in monolayer Cu2 Si based on combined theoretical calculations and angle-resolved photoemission spectroscopy measurements. The Dirac nodal lines in Cu2 Si form two concentric loops centred around the Γ point and are protected by mirror reflection symmetry. Our results establish Cu2 Si as a platform to study the novel physical properties in two-dimensional Dirac materials and provide opportunities to realize high-speed low-dissipation devices. Nodal line semimetals have been observed in three-dimensional materials but are missing in two-dimensional counterparts. Here, Feng et al. report two-dimensional Dirac nodal line fermions protected by mirror reflection symmetry in monolayer Cu2 Si.